Coping Strategies to Mitigate Food Insecurity at Household Level: Evidence From Urban Setting in Addis Ababa, Ethiopia - Sibhatu Biadgilign PhD, MPHE, MSc (SAGE Publishing, 2023)
Food insecurity is the limited or uncertain ability of households to acquire nutritionally adequate and safe foods in socially acceptable ways. There is paucity of empirical evidence on household food insecurity, level of expenditure, and coping strategies in urban setting of Ethiopia. The objective of this paper is to examine the coping strategies of food insecure households in an urban area setting of Addis Ababa, Ethiopia. This study is based on data collected from 632 mothers interviewed in 2017. Multi-stage sampling techniques were carried out to identify the study unit from selected sub-cites. From each sub-city, proportion to population sampling was applied to obtain the sample size. Simple random sampling method was used to select districts in each sub-city. Multivariable logistic regression model was used to identify factors associated with food security status. The most common coping strategies households used in response to food insecurity were: rely on less preferred and less expensive foods, borrow food, or borrow money to buy food and purchase of food on credit. Food insecure households were 3 times more likely to rely on help from a relative or friend outside the household [AOR = 2.37; 95% CI: (1.01, 5.53); P  < .047] compared to food secure households. Similarly, food insecure households were approximately 4 times more likely to limit portions at mealtimes [AOR = 3.55; 95% CI: (1.36, 9.30); P  < .010] compared to food secure households. Furthermore, households with no access to a bank or microfinance savings account were 3 times [AOR = 2.62; 95%: (1.21, 5.66); P  < .014] more likely to become food insecure compared to those with access to financial services. Households rely on less preferred cheap foods or lending to cope with food insecurity in urban settings of Ethiopia. Encouraging households to practice urban gardening, social protection through integrated national safety net programs, and improving access to microfinance services would be vital to address food insecurity among urban households of the country to bring successful social and economic development.